Neurons in the Hippocampus of Crows Lack Responses to Non-spatial Abstract Categories - Ditz, Helen M.; Kupferman, Jennifer K.; Nieder, Andreas (Frontiers in Systems Neuroscience, 2018)
Lesion studies suggest a role of the avian hippocampus in spatial and episodic memory. However, whether the avian hippocampus is also involved in processing categorical information and non-spatial working memory contents remains unknown. To address this question, we trained two crows in a delayed-match-to-sample test to assess and briefly memorize the number of items in dot displays, i.e. their numerosity. We recorded neuronal activity in hippocampus while crows solved this task. Hardly any hippocampal neurons responded to the category ‘numerosity’, during neither sample presentation, nor during the memory delay. This was in striking contrast to previous recordings in the telencephalic association area ‘nidopallium caudolaterale’ (NCL) of the same crows, in which we previously reported an abundance of numerosity-selective and working memory-selective neurons. Our data suggest that categorical information is not processed in the avian hippocampus. This, in turn, argues for dissociated functions of the avian and mammalian hippocampi.